2009
DOI: 10.1007/s00192-009-1061-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of vaginal repairs with and without xenograft reinforcement

Abstract: Sacral neuromodulation has been developed to treat chronic lower urinary tract symptoms, resistant to classical conservative therapy. The suspected mechanisms of action include afferent stimulation of the central nervous system and modulation of activity at the level of the brain. Typical neuromodulation is indicated both in overactivity and in underactivity of the lower urinary tract. In the majority of patients, a unilateral electrode in a sacral foramen and connected to a pulse generator is sufficient to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…Van Kerrebroeck believed that sacral root electrical stimulation could enhance DSM contraction by strengthening somatic afferent inputs to the spinal micturation centre. 29 30 Kovacevic et al reported that PTNS could activate the voiding reflex and alter bladder function. 31 These studies are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Van Kerrebroeck believed that sacral root electrical stimulation could enhance DSM contraction by strengthening somatic afferent inputs to the spinal micturation centre. 29 30 Kovacevic et al reported that PTNS could activate the voiding reflex and alter bladder function. 31 These studies are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from congress abstracts, there are very few studies on the use of Surgisis in pelvic floor repair. These include one randomised controlled trial of women undergoing anterior compartment repair [ 8 ] and three retrospective comparative studies [ 7 , 9 , 10 ]. The randomised trial with 56 patients compared Surgisis with traditional anterior colporrhaphy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, lack of randomisation and small numbers limit interpretation of these data. A comparative study by Mouritsen et al [ 9 ], with a median followup of three years, found better results with Surgisis than with anterior or posterior colporrhaphy, but the difference was not statistically significant. Reid and Luo [ 10 ] compared 108 bridging graft vaginal paravaginal repairs (89 using Surgisis) with 59 native tissue cystocoele repairs [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that biological mesh has unpredictable long-term viability and does not generate new tissue at the implant site that is strong enough [27,28]. The use of a biological graft as a scaffold for MSCs could provide an additional mechanical support to weakened tissues [29].…”
Section: Discussionmentioning
confidence: 99%